2002
DOI: 10.1177/107602960200800403
|View full text |Cite
|
Sign up to set email alerts
|

ProC® Global Assay in the Evaluation of Women with History of Severe Preeclampsia or HELLP Syndrome

Abstract: Preeclampsia/HELLP syndrome has been associated with a high incidence of defects in the protein C pathway and increased anticardiolipin-antibodies/lupus anticoagulants. It is also apparent that thrombophilia is responsible for other pregnancy complications, such as recurrent spontaneous abortion, fetal growth restriction, intrauterine fetal death, and abruptio placentae. ProC Global is a new global dotting assay designed to evaluate the abnormalities in the protein C anticoagulant pathway. It is based on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…ProC Global assay has already been explored in women with recurrent thrombo-emolism [16,17], thromboemolic phenomena under hormonal therapy [25] repeat pregnancy loss [26] and in women with severe pre-eclampsia and HELLP syndrome [27]. Moreover, it has been recently explored in women throughout pregnancy; following ART [11] or spontaneous conception [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…ProC Global assay has already been explored in women with recurrent thrombo-emolism [16,17], thromboemolic phenomena under hormonal therapy [25] repeat pregnancy loss [26] and in women with severe pre-eclampsia and HELLP syndrome [27]. Moreover, it has been recently explored in women throughout pregnancy; following ART [11] or spontaneous conception [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Protein C global assay was previously detected in women with recurrent thromboembolism [16,20], in those with recurrent pregnancy loss [21], and also in women with severe preeclampsia and HELLP syndrome [22]. The test was recently evaluated in women with spontaneous conception [18].…”
Section: Discussionmentioning
confidence: 99%
“…In multicenter studies, abnormal ProC Global assay results were found to be associated with first episode of VTE [22,23] and recurrent VTE [24]. Furthermore, abnormal ProC Global assay results were found to be more common (70%) in women with pregnancy loss, pre-eclampsia, and hemolytic anemia, elevated liver enzymes and low platelet count (HELLP) syndrome compared with healthy women without these complications [25,26].…”
Section: Proc® Global Assay Evaluates Abnormalities In the Protein C mentioning
confidence: 99%